Self‐care of patients with multiple chronic conditions and their caregivers during the COVID‐19 pandemic: A qualitative descriptive study. (30th November 2021) - De Maria, Maddalena; Ferro, Federico; Vellone, Ercole; Ausili, Davide; Luciani, Michela; Matarese, Maria
Abstract: Aims: Explore the self‐care experiences of patients with multiple chronic conditions (MCCs) and caregivers' contributions to patient self‐care during COVID‐19 pandemic. Design: A descriptive qualitative design was used. The COREQ checklist was used for study reporting. Methods: Individual semi‐structured interviews were used to collect data from patients with MCCs and caregivers selected from the dataset of an ongoing longitudinal study. Data analysis was performed through deductive thematic analysis. The middle‐range theory of self‐care of chronic illness, which entails the three dimensions of self‐care maintenance, monitoring and management, was used as a theoretical framework to guide data collection and analysis. Results: A total of 16 patients and 25 caregivers were interviewed from May to June 2020. The participants were mainly women, with a mean age for patients of 76.25 years and caregivers of 45.76 years; the caregivers were mainly the patients' children (72%). During the pandemic, some patients reported remaining unchanged in their self‐care maintenance, monitoring and management behaviours, others intensified their behaviours, and others decreased them. Caregivers played an important role in protecting patients from the risk of contagion COVID‐19 and in ensuring patients' self‐care of chronic diseases through direct and indirect interventions. Conclusions: Critical events can modify the self‐care experiences of chronically ill patients and caregivers' contributions, leading to maintenance, increase or decrease of self‐care and contributions to self‐care behaviours. Impact: Patients with MCCs and their caregivers can react in different ways in their performances of self‐care and contribution to patients' self‐care behaviours when ordinary daily life is disrupted; therefore, nurses should assess such performances during critical events to identify the individuals at risk of reduced self‐care and promote the most suitable healthcare services (e.g. eHealth) to implement individualised interventions.